Comorbidity analysis in obstructive sleep apnea patients (Annals of Medical Research, 2022)
Aim: Obstructive sleep apnea (OSA) is a syndrome that causes complete or partial cessation of breathing and as a result of several pathways, hypertension (HT), type 2 diabetes mellitus (DM), and hyperlipidemia (HL) are usually seen as comorbidities. The main problem in the literature is, due to the presence of some confounders, especially body mass index (BMI), it is still not clear that if OSA is an independent risk factor for these comorbidities. This issue may be shown more clearly with BMI and age-matched subjects since they are strongly related to metabolic diseases and HT. Comparison of the ratios of the presence of DM, HL, and hypertension between the age and BMI matched groups is primarily aimed in the present study to see if moderate and severe OSA could be an independent risk factor for these comorbidities. Materials and Methods: Patients admitted with sleep problems were retrospectively scanned from the patient files and cases with polysomnography and routine blood test were included. The body mass indexes, ages, smoking, and alcohol habits of the cases were noted. Two groups were formed based on polysomnography, taking a threshold value of the apnea-hypopnea index (AHI) of 15. Group 1 had cases with AHI
Keywords: Obstructive sleep apnea; Hypertension; Diabetes mellitus; Hyperlipidemia; Metabolic diseases